Clinical characteristics and outcomes in those with primary extrahepatic malignancy and malignant ascites - Alshuwaykh, Omar; Cheung, Amanda; Goel, Aparna; Kwong, Allison; Dhanasekaran, Renumathy; Ghaziani, T. Tara; Ahmed, Aijaz; Daugherty, Tami; Dronamraju, Deepti; Kumari, Radhika; Nguyen, Mindie; Kim, W. Ray; et al. (BMC gastroenterology, 2022)
Background Malignancy-related ascites accounts for approximately 10% of causes of ascites. Our AIM was to characterize the ascites fluid and correlate clinical outcomes in those with extrahepatic malignancy and ascites. Methods 241 subjects with extrahepatic solid tumors and ascites were reviewed from 1/1/2000 to 12/31/2019, 119 without liver metastasis and 122 with liver metastasis. Results Ascites fluid consistent with peritoneal carcinomatosis (PC) was most common, 150/241 (62%), followed by fluid reflecting the presence of portal hypertension (PH), 69/241 (29%). 22/241 (9%) had low SAAG and low ascites fluid total protein, with evidence of PC on cytology and or imaging in 20/22. Lung cancer was the most common malignancy in subjects with ascites due to PC at 36/150 (24%), pancreatic cancer was the most common in subjects with ascites with features of PH at 16/69 (23%). Chemotherapy or immunotherapy alone was the most common management approach. Significantly higher 5-year, 3-year and 1-year mortality rate were noted in subjects with evidence of PC on cytology/imaging versus subjects with no evidence of PC, and in subjects with liver metastasis compared to subjects without liver metastasis. Subjects with pancreatic cancer and evidence of PC on cytology/imaging had higher 1 and 5-year mortality rates compared to subjects without PC. Conclusions Ascites in solid tumor malignancy is most commonly due to PC. We also observed ascites fluid with characteristics of PH in 29% of subjects. Higher mortality rates in subjects with peritoneal carcinomatosis and liver metastasis were noted. These findings may help inform prognosis and treatment strategies.